Ethanol exposure and isolated traumatic brain injury. Issue 12 (December 2015) - Brennan, James H.; Bernard, Stephen; Cameron, Peter A.; Olaussen, Alexander; Fitzgerald, Mark C.; Rosenfeld, Jeffrey V.; Mitra, Biswadev
Abstract: This study aims to investigate an association between ethanol exposure and in-hospital mortality among patients with isolated traumatic brain injury (iTBI). Ethanol exposure is associated with a substantially increased risk of sustaining an iTBI. However, once an iTBI has been sustained, it is unclear whether ethanol exposure is neuroprotective or harmful. We conducted a retrospective review of patients who presented between 2006 and 2012 and were entered into the Alfred Hospital trauma registry. The patients who presented with iTBI, as defined by a head abbreviated injury scale (AIS) score ⩾3 and all other body regions with AIS < 3, and who had ethanol levels recorded on admission, were eligible for inclusion. The association between ethanol exposure as a continuous variable, and in-hospital mortality, was explored using multivariable logistic regression analysis. There were 1688 patients with iTBI who met the inclusion criteria, 577 (34.2%) of whom tested positive for ethanol. Ethanol exposure was not significantly associated with a change in the in-hospital mortality rate (adjusted odds ratio 1.01; 95% confidence interval 1.00–1.02; p  = 0.19). A substantial proportion of patients with iTBI were exposed to ethanol, but ethanol exposure was not independently associated with a change in mortality rate following iTBI. Any neuroprotection or harm from ethanol exposure was not conclusive, requiring further prospective trials.